2007
DOI: 10.1007/s00421-006-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Isocapnic hyperpnea training improves performance in competitive male runners

Abstract: The effects of voluntary isocapnic hyperpnea (VIH) training (10 h over 4 weeks, 30 min/day) on ventilatory system and running performance were studied in 15 male competitive runners, 8 of whom trained twice weekly for 3 more months. Control subjects (n = 7) performed sham-VIH. Vital capacity (VC), FEV1, maximum voluntary ventilation (MVV), maximal inspiratory and expiratory mouth pressures, VO2max, 4-mile run time, treadmill run time to exhaustion at 80% VO2max, serum lactate, total ventilation (V(E)), oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
60
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 39 publications
13
60
1
Order By: Relevance
“…With the exception of one study (37) evidence suggests that placebo effects associated with RMT interventions are minimal (12,15,18,35,36,41) thus we feel that the physiological changes observed after IMT in this study are unlikely to be the result of greater subject expectation and/or motivation. Notwithstanding this, a limitation of our study is that a placebo was not used, which may have influenced outcome measures in the control group.…”
Section: Paragraph Number 27mentioning
confidence: 68%
“…With the exception of one study (37) evidence suggests that placebo effects associated with RMT interventions are minimal (12,15,18,35,36,41) thus we feel that the physiological changes observed after IMT in this study are unlikely to be the result of greater subject expectation and/or motivation. Notwithstanding this, a limitation of our study is that a placebo was not used, which may have influenced outcome measures in the control group.…”
Section: Paragraph Number 27mentioning
confidence: 68%
“…In healthy people and in athletes, the inability to sustain high levels of ventilation can restrict maximal aerobic capacity [7,12,31]. It has been shown that IMT without the addition of systemic exercise may result in quantitative outcomes [9,10,17,32]. The total mechanical work done during breathing is the sum of all elastic and non-elastic work components.…”
Section: Discussionmentioning
confidence: 99%
“…This notion contradicts the traditional view that the small mass of the respiratory muscles (estimated at around 960 g (Freedman et al 1983)) and their large oxidative capacity precludes any systemically relevant lactate exchange (Wetter and Dempsey 2000 Romer et al 2002b) and volitional isocapnic hyperpnoea training (endurance-training stimulus) (Leddy et al 2007;Spengler et al 1999), with up to 52% of variation in post-training whole-body exercise performance improvement accounted for by the reduced [lac -] B (Romer et al 2002b). …”
Section: Introductionmentioning
confidence: 93%